MAPK phosphatase-1 (MKP-1) expression is up-regulated by hCG/cAMP and modulates steroidogenesis in MA-10 Leydig cells - Brion, Laura (2011)
MAP kinases (MAPKs), such as ERK1/2, exert profound effects on a variety of physiological processes. In steroidogenic cells, ERK1/2 are involved in the expression and activation of steroidogenic acute regulatory protein, which plays a central role in the regulation of steroidogenesis. In MA-10 Leydig cells, LH and chorionic gonadotropin (CG) trigger transient ERK1/2 activation via protein kinase A, although the events that lead to ERK1/2 inactivation are not fully described. Here, we describe the hormonal regulation of MAPK phosphatase-1 (MKP-1), an enzyme that inactivates MAPKs, in MA-10 cells. In our experiments, human CG (hCG)/cAMP stimulation rapidly and transiently increased MKP-1 mRNA levels by a transcriptional action. This effect was accompanied by an increase in protein levels in both nuclear and mitochondrial compartments. In cells transiently expressing flag-MKP-1 protein, hCG/cAMP promoted the accumulation of the recombinant protein in a time-dependent manner (10-fold at 1 h). Moreover, hCG/cAMP triggered ERK1/2-dependent MKP-1 phosphorylation. The blockade of cAMP-induced MAPK kinase/ERK activation abated MKP-1 phosphorylation but only partially reduced flag-MKP-1 protein accumulation. Together, these results suggest that hCG regulates MKP-1 at transcriptional and posttranslational level, protein phosphorylation being one of the mechanisms involved in this regulation. Our study also demonstrates that MKP-1 overexpression reduces the effects of cAMP on ERK1/2 phosphorylation, steroidogenic acute regulatory gene promoter activity, mRNA levels, and steroidogenesis, whereas MKP-1 down-regulation by small interfering RNA produces opposite effects. In summary, our data demonstrate that hCG regulates MKP-1 expression at multiple stages as a negative feedback regulatory mechanism to modulate the hormonal action on ERK1/2 activity and steroidogenesis.